Isolation of Candida spp. from mastitic bovine milk in Brazil - dos Santos, R. D.; Marin, J. M. (Springer, 2005)
The purpose of this study was to isolate yeast (Candida) from the quarter milk of cow udders from 37 dairy farms in Brazil and to identify the different species involved in mastitis. The samples were collected between October 2002 and February 2003. Two-hundred-and-sixty milk samples from cows with clinical and subclinical mastitis were examined. Milk samples were plated onto Blood agar, Mac Conkey agar and Sabouraud dextrose agar. Forty-five (17.3%) samples were positive for the genus Candida. The Candida species isolated were C. krusei (44.5%), C. rugosa (24.5%), C. albicans (8.9%), C. guilliermondii (8.9%), and others (13.2%). We also isolated Escherichia coli (26.5%), coagulase-positive Staphylococcus (25.0%), Streptococcus spp. (8.1%), Enterobacter spp. (8.1%), and other fungi (8.1%), among others.
Keywords: cattle; mastitis; milk; yeast